2020
DOI: 10.1108/ijchm-02-2019-0185
|View full text |Cite
|
Sign up to set email alerts
|

Religion and entrepreneurship in hospitality and tourism

Abstract: Purpose This study aims to provide a theoretical account of the nexus of religion and entrepreneurship in hospitality and tourism (H&T) by considering the influences of religion on entrepreneurial motivation, acquisition of resources for entrepreneurship and entrepreneurial behaviour. Design/methodology/approach The authors synthesise research and theory on religion and entrepreneurship and apply it within H&T, taking into account the specificities of the industry. Specifically, they pooled together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 130 publications
0
49
0
2
Order By: Relevance
“…The fundamental role religion plays in shaping Islamic travel and hospitality consumption has been acknowledged; they should "continue practicing their religion…in both Muslim and non-Muslim countries" (Han et al, 2019, p.153). Thus, while allowances are made for Muslims travelling under specific circumstances, they are generally expected to consume goods permitted by the Quran (e.g., halal food) and gender segregation is often preferred when using hospitality facilities (Farmaki et al, 2020;Yalinay et al, 2019). Muslim's thus typically seek halal-friendly products and practices during their travels, alongside facilities that satisfy their religious needs.…”
Section: Recent Years Have Witnessed Increased Academic Attention On mentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental role religion plays in shaping Islamic travel and hospitality consumption has been acknowledged; they should "continue practicing their religion…in both Muslim and non-Muslim countries" (Han et al, 2019, p.153). Thus, while allowances are made for Muslims travelling under specific circumstances, they are generally expected to consume goods permitted by the Quran (e.g., halal food) and gender segregation is often preferred when using hospitality facilities (Farmaki et al, 2020;Yalinay et al, 2019). Muslim's thus typically seek halal-friendly products and practices during their travels, alongside facilities that satisfy their religious needs.…”
Section: Recent Years Have Witnessed Increased Academic Attention On mentioning
confidence: 99%
“…al., 2013; women are expected to cover their bodies and, in some cases, faces; and genders often use separate hospitality facilities. Nevertheless, followers of the same religion do not always practice in the same way, with faith serving as base influence as opposed to steadfast dogma (Farmaki et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These studies have identified how the religious belief system can have an important consequence for entrepreneurial attitude. However, variations exist in research about how religion influences entrepreneurship (Farmaki et al, 2020). Past studies (Nichter and Goldmark, 2009;Hamdan, 2005) focused on how religion inhibits start-up of entrepreneurial activity or expansion of existing ones.…”
Section: Socio-cultural Environmentmentioning
confidence: 99%
“…Studying religion in hospitality management, however, is still in the beginning stage (Gursoy et al, 2017). Most recently in hospitality literature, researchers have explained how religiosity shapes entrepreneurs' values and entrepreneurship behavior (Farmaki et al, 2020;Gursoy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…leadership and hierarchy in religious organizations) factors in the religion and the group(s), shaping religious group-based social perception (Turner, 1987). Such religious group-based social perception could then be transferred by employees as spiritual higher-order guiding principles for their attitudes and behaviors at the workplace such as ethical beliefs (Vitell et al, 2006;Vitell et al, 2007), entrepreneurship behaviors (Farmaki et al, 2020;Gursoy et al, 2017) and environmental action (Sherkat and Ellison, 2007). As an example of the religiositydriven mental and behavioral changes in social groups, McNicholl (2018) found that African American Buddhists (e.g.…”
Section: Introductionmentioning
confidence: 99%